Corrosion of Low Carbon Steel in Sulphuric Acid Solution in Presence of Furane-Halides Mixture - El-Din Kamel Gomma, Gamal (Asian Journal of Chemistry, 2010)
The corrosion behaviour of low carbon steel in stagnant aerated sulphuric acid solution and in presence of furane-halide mixture was studied. Furane inhibits the cathodic reaction, but halides inhibit the anodic reaction. These results form the polarisation technique. Weight-loss technique illustrates that the temperature increases the corrosion rate in the range (30º–85ºC) in presence and in absence of inhibitors. The apparent activation energy is 12.4 kcal/mole.